Pengaruh Hypnobreastfeeding Terhadap Self Efficacy Menyusui Pada Ibu Postpartum di Rumah Sakit Umum Pusat Dr Mohammad Hoesin Palembang Tahun 2024 - Selvi Adelia (Masker Medika, 2024)
Introduction: Hypnobreastfeeding is an effort to speed up the breastfeeding process by giving affirmations or positive suggestions to the mother. Breastfeeding self-efficacy is a variable that predicts whether the mother chooses to breastfeed or not, efforts to breastfeed the baby and how to deal with breastfeeding difficulties Methods: Study design is quasi experimental research design with a pre and posttest approach with control and intervention groups. Data collection was carried out in April – May 2024 with a population of postpartum mothers who gave birth at Dr Mohammad Hoesin Hospital, Palembang. The 32 research respondents consisted of 16 intervention groups and 16 controls. Hypnobreastfeeding once a day for 7 days with a duration of 45 minutes. Self-efficacy was measured using the breastfeeding self-efficacy scale short form (BSES-SF). Bivariate analysis using repeated independent t-test.. Results: The breastfeeding self-efficacy score in the group with hypnobreastfeeding increased significantly in measurements from pretest to posttest with p= 0.001, while in the control group with standard education the increase in breastfeeding self-efficacy score from pretest to posttest was not significant with p=0.086. Hypnobreastfeeding is more effective in increasing breastfeeding self-efficacy than standard education with a value of p=0.001 Discussion: There is an effect of providing hypnbreastfeeding intervention on breastfeeding self-efficacy in postpartum mothers at Dr Mohammad Hospital Palembang in 2024.